Hyponatremia in Ischemic Stroke Patients Presented to the Neurology Department at the Nephrology Institute of Kidney Disease - Abdul Haseeb, Rahmat Ali Khan, Waqas Sardar, Usman Ali, Raza Muhammad Khan, Saad Hanan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aims to assess the prevalence of hyponatremia in ischemic stroke patients. Material and Methods: This study was a descriptive cross-sectional study. This research included all inpatients and outpatients at the Nephrology Institute of Kidney Disease from January 01, 2021, to December 31, 2022. A total of 214 people who had had a stroke were included in the analysis. On an official Proforma, the study’s goals, potential harms, and potential rewards were laid out for the participant. Results: The study examined 214 people who had had an ischemic stroke. The average age of the patients was above 35. Patients’ ages averaged 70 years. Male patients comprised 64% of the total, with 76 female patients making up 36% of the sample size. The Incidence of hyponatremia in individuals with ischemic stroke was 24%. The prevalence of hyponatremia increased dramatically between the ages of 51 and 75. Patients with hypertension were more likely to have hyponatremia than those without hypertension (31% vs. 12%, p=0.04). Diabetes doubled the Incidence of hyponatremia, which affected both sexes equally. (60 vs. 20 percent) The Incidence of hyponatremia in the context of an ischemic stroke was shown to be doubled in those with a high body mass index (BMI). (35% vs. 19%) Conclusion: There was a significant incidence and frequency of hyponatremia after stroke. The prognosis and mortality rate of stroke patients are already poor, and hyponatremia worsens the situation. Keywords: Inappropriate Antidiuretic Hormone Secretion, Cerebral Salt Wasting Syndrome, Hyponatremia, Stroke, Ischemic, and Hyponatremia.